2022
DOI: 10.5772/intechopen.93695
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Associated Oral and Periodontal Health Based on Retrospective Panoramic Radiographic Analysis of Alveolar Bone Loss

Abstract: Gender-based heterogeneity in periodontal disease has been witnessed in the recent past with huge mounting evidence. The composite effect of sex-based genetic structure and the sex steroid hormones runs in line with the corresponding genderrelated differences in risk for chronic periodontitis. Since estrogens, the predominant sex hormones in women, show immune protective and anti-inflammatory effects in hormonally active premenopausal women, they show better periodontal status compared to age-matched men. Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 165 publications
(175 reference statements)
1
0
0
Order By: Relevance
“…In the current study, similar to previous publications 45,46 , males demonstrated a greater risk of developing worse periodontal conditions compared with females. Sanadi et al 47 assessed the oral hygiene of 209 dental students and found gender differences, reflecting a greater incidence of gingival disease in males than in females.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, similar to previous publications 45,46 , males demonstrated a greater risk of developing worse periodontal conditions compared with females. Sanadi et al 47 assessed the oral hygiene of 209 dental students and found gender differences, reflecting a greater incidence of gingival disease in males than in females.…”
Section: Discussionsupporting
confidence: 92%
“…28 In terms of sex-related differences in the prevalence of periodontitis and diabetes, the current study's data show that men had higher rates of both conditions than women did, which is consistent with findings from studies by Anna Nordström et al on the prevalence of diabetes and Ashish Jain et al on sex-related differences in the prevalence of periodontitis. 42,43 This study's findings on PI, CPITN, and OHI scores were in agreement with a study by Roberto Del Giudice et al 44 on their favourable correlation with IL-6 levels. By comparing the levels of IL-6 in GCF between diabetic subjects and non-diabetic (healthy subjects) without periodontitis as well as between the levels of IL-6 in GCF before and after periodontal management, more research is needed to understand the function and potential mechanism of IL-6 in the pathogenesis of diabetes and periodontitis.…”
Section: Discussionsupporting
confidence: 91%